Design optimization on Ross yoke mechanism for stirling engine - Jaisue, Apirat; Kansuwan, Panya; Kwankaomeng, Sutapat (My University, 2026)
This paper presents a design analysis and optimization of an Alpha-type Stirling engine with a double-acting mechanism. The engine has four cylinders with a piston diameter and length of 60 mm and 113.2 mm, respectively. Using the Ross yoke with a double-acting mechanism, the engine has a swept volume and stroke of 384.69 cm3 and 34 mm. The working gas is 10 bar pressurized air. ADAMS software is used to access dynamic balancing and kinematic analysis. Operating characteristics and performance were investigated and parameterized for optimization. Minimizing the stroke difference of four pistons, uniform piston stroke, is the objective function with the top and bottom-dead constraints. The length of the rocking lever attached to the yoke link influences the smooth reciprocating of all pistons. The simulation results with searching method optimization show the dynamic motion of the Ross yoke mechanism that can be adjusted to the optimal piston stroke with the suitable length of the rocking lever.